2017
DOI: 10.1016/j.vetmic.2017.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of antigenicity and pathogenicity reveals major differences among QX-like infectious bronchitis viruses and other serotypes

Abstract: Avian coronavirus infectious bronchitis virus (IBV) causes considerable damage to the poultry industry worldwide and the proportion of QX-like genotype isolates have increased over time. Here, to better understand the antigenicity and pathogenicity of this genotype, we conducted sequence analyses, cross neutralization tests, and also examined the pathogenicity of two strains, SD and SZ. Sequence analyses revealed that SD and SZ isolates belong to the QX-like IBV genotype and share high homology in their full-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 37 publications
(45 reference statements)
2
17
0
Order By: Relevance
“…In the present study, regulation of gene expression in chicken kidney cells infected with nephropathogenic IBV was analyzed. Chicks inoculated virulent strains such as SCDY2 and SCK2 exhibited severe clinical signs and renal lesions as reported previously [12,34,35] and also resulted in modification of gene expression and activation of apoptosis in kidney cells. However, apoptosis induced by the two viral strains is quite different.…”
Section: Induction Of Apoptosis In Virulent Nephropathogenic Ibv Infesupporting
confidence: 72%
“…In the present study, regulation of gene expression in chicken kidney cells infected with nephropathogenic IBV was analyzed. Chicks inoculated virulent strains such as SCDY2 and SCK2 exhibited severe clinical signs and renal lesions as reported previously [12,34,35] and also resulted in modification of gene expression and activation of apoptosis in kidney cells. However, apoptosis induced by the two viral strains is quite different.…”
Section: Induction Of Apoptosis In Virulent Nephropathogenic Ibv Infesupporting
confidence: 72%
“…The cross-reactivity R values indicated that the seven QX-type isolates were classified into the same SCZY3-serotype, which was different from H120 and 4/91 (R < 0.11) [12,25]. It has been reported that some QX-type strains showed distant relationships with other representative strains of the classical IBV serotypes [20]. The results indicated that different QX-type isolates were important agents for IBV outbreaks in China, and a new vaccine strain should be used for the prevention and control of IB.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, it is important to understand the antigenicity and pathogenicity of QX-type IBV field isolates for the prevention and control of IB. It has been reported that the antigenicity and virulence vary between different genotypes [12,20], and no systematic comparison among QX-type IBVs has been conducted. In our study, eight QX-type IBVs were isolated from H120 and 4/91 vaccinated chickens in China, and their antigenicity and pathogenicity were analyzed for understanding the epidemiology and evolution of IBVs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phylogenetic analyses showed that the IBV isolates that clustered with QX were mainly Chinese isolates (Zhao et al, 2016). These results further indicated that IBV isolates prevalent in China were evolutionarily distant from Massachusetts (Mass)-type strains (Terregino et al, 2008;Abro et al, 2012;Yan et al, 2017). Understanding the pathogenic mechanism and molecular characteristics of circulating strains could significantly facilitate the development of vaccines that provide efficient protection against the highly variable IBV.…”
Section: Introductionmentioning
confidence: 89%